The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3102/10769986221099906
|View full text |Cite
|
Sign up to set email alerts
|

Speed–Accuracy Trade-Off? Not So Fast: Marginal Changes in Speed Have Inconsistent Relationships With Accuracy in Real-World Settings

Abstract: The speed–accuracy trade-off (SAT) suggests that time constraints reduce response accuracy. Its relevance in observational settings—where response time (RT) may not be constrained but respondent speed may still vary—is unclear. Using 29 data sets containing data from cognitive tasks, we use a flexible method for identification of the SAT (which we test in extensive simulation studies) to probe whether the SAT holds. We find inconsistent relationships between time and accuracy; marginal increases in time use fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…This is illustrated by recent research, which found that accuracy cannot always be predicted by reaction time. Therefore, a longer time can indicate either increased or reduced accuracy (32). This issue may be caused by characteristics that vary between male and female traits.…”
Section: Ebpm Reaction Time Performancementioning
confidence: 99%
“…This is illustrated by recent research, which found that accuracy cannot always be predicted by reaction time. Therefore, a longer time can indicate either increased or reduced accuracy (32). This issue may be caused by characteristics that vary between male and female traits.…”
Section: Ebpm Reaction Time Performancementioning
confidence: 99%
“…As a illustration of an alternative approach, we conducted a study of the speed-accuracy tradeoff's relevance in observational data using a data-rich paradigm [2]. Our approach suggested that a wide variety of conditional accuracy functions (CAFs) may be observed in empirical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [25,26] has developed DIF methods to detect time use differences between groups, and has shown them to be related to response accuracy in tests like PISA. The relationship between time use and accuracy has been shown to exist even after controlling for item and person effects, and can also take complicated functional forms [27,28].…”
Section: Introduction Introductionmentioning
confidence: 99%
“…These studies typically use experimental interventions designed to force respondents to respond at different speeds. However, more recent work focuses on identification of the CAF in observational settings [34,27] in an attempt to ask whether idiosyncratic within-person variation in speed is associated with variation in accuracy. We build on this approach here.…”
Section: Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation